Feasibility of Focused Stepping Practice During Inpatient Rehabilitation Poststroke and Potential Contributions to Mobility Outcomes. (November 2015) - Hornby, T. George; Holleran, Carey L.; Leddy, Abigail L.; Hennessy, Patrick; Leech, Kristan A.; Connolly, Mark; Moore, Jennifer L.; Straube, Donald; Lovell, Linda; Roth, Elliot
Background . Optimal physical therapy strategies to maximize locomotor function in patients early poststroke are not well established. Emerging data indicate that substantial amounts of task-specific stepping practice may improve locomotor function, although stepping practice provided during inpatient rehabilitation is limited (<300 steps/session). Objective. The purpose of this investigation was to determine the feasibility of providing focused stepping training to patients early poststroke and its potential association with walking and other mobility outcomes. Methods . Daily stepping was recorded on 201 patients <6 months poststroke (80% < 1 month) during inpatient rehabilitation following implementation of a focused training program to maximize stepping practice during clinical physical therapy sessions. Primary outcomes included distance and physical assistance required during a 6-minute walk test (6MWT) and balance using the Berg Balance Scale (BBS). Retrospective data analysis included multiple regression techniques to evaluate the contributions of demographics, training activities, and baseline motor function to primary outcomes at discharge. Results . Median stepping activity recorded from patients was 1516 steps/d, which is 5 to 6 times greater than that typically observed. The number of steps per day was positively correlated with both discharge 6MWT and BBS and improvements from baseline (changes; r = 0.40-0.87), independently contributing 10% to 31% of the total variance. Stepping activity also predicted level of assistance at discharge and discharge location (home vs other facility). Conclusion. Providing focused, repeated stepping training was feasible early poststroke during inpatient rehabilitation and was related to mobility outcomes. Further research is required to evaluate the effectiveness of these training strategies on short- or long-term mobility outcomes as compared with conventional interventions.